2015
DOI: 10.1016/j.compositesa.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear tensile behaviour of elementary hemp fibres. Part II: Modelling using an anisotropic viscoelastic constitutive law in a material rotating frame

Abstract: A 3D viscoelastic model is presented, based on the use of finite element method for the study of the nonlinear tensile behaviour of hemp fibres. On the basis of an experimental investigation, Part I of this study (Placet, Cisse and Boubakar, Composites Part A 56:319-327, 2014) proposed a scenario based on several physical mechanisms, in order to explain the nonlinear behaviour of such fibres. These mechanisms included viscoelastic strain, cellulose microfibril reorientation, and shear strain-induced crystallis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…13b), we can notice that the average cyclic-RH creep rate is higher than the constant- This observation also supports the sorption-induced stressgradient explanations proposed by these authors. In a previous work [19], we showed that when considering that the fibre has a constant and cylindrical cross section along its length and using a theoretical model, an axial stress gradient is established across the fibre wall under tensile loading. The axial stress is the highest at the inner face of the cell wall and progressively decreases with the thickness of the cell wall.…”
Section: Moisture Levelmentioning
confidence: 99%
“…13b), we can notice that the average cyclic-RH creep rate is higher than the constant- This observation also supports the sorption-induced stressgradient explanations proposed by these authors. In a previous work [19], we showed that when considering that the fibre has a constant and cylindrical cross section along its length and using a theoretical model, an axial stress gradient is established across the fibre wall under tensile loading. The axial stress is the highest at the inner face of the cell wall and progressively decreases with the thickness of the cell wall.…”
Section: Moisture Levelmentioning
confidence: 99%
“…The 3D model used for this study is based on a model previously developed in our team. It is fully described in [16] and [14]. It is based on macroscopic considerations and uses the continuum mechanics formulation.…”
Section: Modellingmentioning
confidence: 99%
“…In a previous work [27], our team proposed a scenario based on several mechanisms including viscoelastic strain, cellulose microfibrils reorientation and shear strain-induced crystallisation of the amorphous paracrystalline components. These mechanisms were then modelled through an anisotropic viscoelastic constitutive law, describing finite tranformations through a material rotating frame formulation [16]. Results showed that this model is able to correctly simulate the shape of the experimentally observed tensile curves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…non-linear stress-strain response) Shah 2013;Wambua et al 2003). Stemming from the latter is another important bottleneck-our inability to accurately model the properties and behaviour of plant fibres (Trivaudey et al 2015) and their composites (Andersons et al 2015;Shah 2016;Summerscales et al 2013;Virk 2010;Virk et al 2012).…”
Section: Introductionmentioning
confidence: 99%